DENSITAS ENERGI KONSUMSI, STATUS GIZI, DAN DAYA INGAT SESAAT ANAK USIA SEKOLAH DASAR - Annisa, Pamila Adhi; Tanziha, Ikeu (Jurnal Gizi dan Pangan, 2014)
The aim of this study was to analyze the correlation between dietary energy density, nutritional status and short term memory of elementary students. Design of this study was a cross sectional with purposive sampling 111 elementary school students in Bogor. Children’s allowance, parent’s education and income, nutritional knowledge, food consumption, physical activity, and short term memory were analyzed by chi square and logistic regression. The method used to measure the short term memory was a serial recall with the word list tool. Measurement of short term memory was two times (09.00 pm and 11.00 pm). The results showed that most of student consumed high energy density food with average density was 2.13 kcal/g for girls and 1.98 kcal/g for boys. Children’s allowance and mother’s education were significantly correlated with dietary energy density. Most of them had normal nutritional status but 27% of them were overweight and obese. Nutritional knowledge and breakfast habit were significantly correlated with nutritional status. Only nutritional knowledge and nutritional status has significantly influence the short term memory.